Konsep Pendidikan Keluarga Dalam Perspektif Al-Qur'an dan Hadis - Herlina Herlina (Fakultas Syariah IAIN Laa Roiba Bogor, 2024)
The role of the family in the educational process, is an inevitable necessity, this is because the important role of the family as the environment of origin, and also the first environment for humans. Thie shows, the existence of the family is very important, in supporting the achievement of educational goals. Facts and reality in the field show that, the role of the family today, has not shown its maximum effort as the main educational institution, so that there is a practice of violence in the family, both against wife and child, which is certainly very contradictory basic principles in the process of education. The presence of this article, intended to explore the important role of the family, in the educational process bassed on the perspective of the Qur'an and Hadith. This exploration is intended to gain a fundamental essence in the process of family education, so as to provide a new perspective on the perceiving of the faimily as an important part of the humanizing process. Keywords: Education, Family, Qur'an, and Hadith.